Pengaruh Kesejahteraan, Hubungan Antar Rekan Kerja dan Pimpinan, Mutu Supervisi dan Promosi Terhadap Loyalitas Karyawan (Studi Kasus Di Kantor Direksi PT. Perkebunan Nusantara III Medan, Sumatera Utara) - GULTOM, ROSMAULI AGUSTINA; USTRIYANA, I NYOMAN GEDE; AGUNG, I DEWA GEDE (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2021)
The Influence of Welfare, Relationships Between Colleagues and Leaders, The Quality of Supervision and Promotion of Employee Loyalty (Case Study of PT. Perkebunan Nusantara III Medan, North Sumatra) The purpose of this study is to analyze the influence of welfare, the relationship between colleagues and leaders, the quality of supervision and promotion on employee loyalty in the office of the board of directors of PT. Perkebunan Nusantara III Medan, North Sumatra. The sample in this study was determined by using the Slovin formula. The sample consists of 88 respondents, 23 management employees and 65 implementing employees using the proportional sampling method. Data collection was done through documentation and interviews using a questionnaire and variables were measured using likert scale. Data was analyzed using SEM SmartPLS analysis. The results show that the welfare factor and the quality of supervision has a significant effect on employee loyalty. The relationship between colleagues and leadership and promotion has no significant effect on employee loyalty. Suggestions that can be given from the results of this study to PT. Perkebunan Nusantara III Medan is to improve employee welfare and quality of supervision to increase employee loyalty.